Motivations for people with cognitive impairment to complete an advance research directive – a qualitative interview study - Karin Jongsma; Julia Perry; Silke Schicktanz; Katrin Radenbach (BMC Psychiatry, 2020)
Abstract Background Research with persons with dementia is important to better understand the causes of dementia and to develop more effective diagnostics, therapies, and preventive measures. Advance Research Directives (ARDs) have been suggested as a possible solution to include persons with dementia in research in an ethically sound way. Little is known about how people, especially those affected by cognitive impairment, understand and regard the use of ARDs, as empirical studies are mainly conducted with healthy, non-cognitively impaired, participants. Methods This qualitative study, a sub-study of a larger study on the evaluation of ARDs in the context of dementia research in Germany, consists of semi-structured in-depth interviews with 24 persons with cognitive impairment. Results Our results indicate that most participants consider ARDs a valuable tool for allowing them to make their own decisions. Many would prefer to draft an ARD when they are still healthy or soon after the diagnosis of cognitive impairment. Participants suggested that the completion of ARDs can be advanced with the provision of practical support and increased dissemination of information on ARDs in society. Conclusion Persons with subjective or mild cognitive impairment (SCI/MCI) suggested several motivating factors and concerns for completing an ARD. Clinicians need to be trained to accommodate patients’ needs for sufficient and adequate information. Furthermore, a standardised, partly pre-formulated template could be helpful for drafting an ARD. As such tested templates are currently not yet available, this addresses the urgent need for more translational and implementation research for the use of ARDs.